2012
DOI: 10.1007/s00264-012-1624-4
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal versus transgluteal approach for hip hemiarthroplasty: an analysis of early complications in seven hundred and four consecutive cases

Abstract: Purpose Hemiarthroplasty (HA) is an established treatment for femoral neck fractures of the elderly. Several surgical approaches are currently used including dorsal and transgluteal. It is still unclear whether one approach may be advantageous. We compared early complication rates after dorsal and transgluteal approaches. Methods We retrospectively analysed a cohort including 704 consecutive patients who received HA for femoral neck fracture; 212 male and 492 female patients were included, and the mean age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 22 publications
(24 reference statements)
2
44
1
1
Order By: Relevance
“…In a recently pub- lished randomized, controlled trial involving 216 patients with hip fractures treated with HA, performed either with a lateral or a posterior approach, no differences could be found regarding residual pain or regain of walking ability . Biber et al (2012) conducted a retrospective study on 704 patients in 2012 and concluded that there was no difference between the posterior approach and the direct lateral approach regarding early surgical complications. However, the posterior approach predisposed to dislocation whereas the direct lateral approach predisposed to hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently pub- lished randomized, controlled trial involving 216 patients with hip fractures treated with HA, performed either with a lateral or a posterior approach, no differences could be found regarding residual pain or regain of walking ability . Biber et al (2012) conducted a retrospective study on 704 patients in 2012 and concluded that there was no difference between the posterior approach and the direct lateral approach regarding early surgical complications. However, the posterior approach predisposed to dislocation whereas the direct lateral approach predisposed to hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Biber et al. (2012) conducted a retrospective study on 704 patients in 2012 and concluded that there was no difference between the posterior approach and the direct lateral approach regarding early surgical complications. However, the posterior approach predisposed to dislocation whereas the direct lateral approach predisposed to hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…The closed reduction manoeuvre routinely uses traction, adduction and internal rotation. If intact, especially the obliquely from inferior lateral to posterior medial running inferior retinaculum of Weitbrecht will assist the reduction manoeuvre in most cases [30,31]. If disrupted, a closed reduction manoeuvre will be difficult to impossible to obtain.…”
Section: Discussionmentioning
confidence: 99%